Overexploitation Of Sand Mining Leading To Imaginary Landscape: Research-Based Creation - I Wayan Setem (Mudra Jurnal Seni Budaya, 2017)
An art has something to do with form and content (shape and the meaning attached to it). When an artist intends to add philosophical value to his creation, he enters two aesthetic exploration spaces; they are the aesthetic concept and the artistic exploration. â€œThe structure of the form shows â€œthe faceâ€ of an art work which cannot be separated from how material should be processed, and the â€œaesthetic structureâ€ treats every â€œaesthetic thingâ€ as an entity which is caught as a combination of the quality of perception and the common sense processing which are drawn into the metaphysical, ethic, axiological, and epistemological (philosophical) dimensions. Similarly, the ideas which are related to the fine arts of which the subject matter is the overexploitation of the sand mining should be processed in the phases of concepts with aesthetic dimension before they are retransformed in the visual stage; therefore, the creative process and the idioms chosen become highly subjective. It is easy to explain every phase in the creation process, and the visual idioms chosen can be generalized, clarified, verified, and concluded in the level of objectivity. The theoretical conception of the visual value becomes multi interpretations and rich in meaning (positive), as the value of its articulation contains symbols and metaphors.Seni adalah bentuk dan isi (wujud dan makna yang melekat). Ketika pengkarya ingin memberikan bobot filsafati pada karyanya, maka pengkarya memasuki dua ruang penjelajahan estetika, yaitu konsep estetik dan eksplorasi artistik. â€Struktur bentukâ€ menunjukkan â€wajahâ€ suatu karya seni dengan pengolahan material, sedangkan â€struktur estetikâ€ meletakkan segala hal yang â€estetikâ€ sebagai suatu entitas yang ditangkap dalam keterpaduan antara kwalitas persepsi dengan pengolahan akal budi yang ditarik kedalam dimensi-dimensi metafisik, etik, aksiologik, dan epistemologik (filsafati). Seperti ide-ide dalam seni rupa yang yang bertitik tolak (subject matter) overeksploitasi penambangan pasir, harus diolah dalam tataran konsep-konsep yang berdimensi estetik, kemudian ditransformasikan lagi dalam tataran visual, maka proses kreatif dan pilihan-pilihan idiom-idiom visualnya menjadi sangat subjektif. Tidaklah mudah dijelaskan setiap tahapan dalam proses kreasi dan pilihan idiom-idiom visual tersebut dapat digeneralisir, diklasifikasi, diverifikasi, dan disimpulkan dalam tataran obyektivitas. Pemahaman teoritik kegambaran visikal (nilai visual) menjadi multi interpretasi dan kaya makna (positif), karena nilai kebentukkannya mengandung simbol-simbol dan metafora-metafora.